THE IMPORTANCE OF SOCIALIZATION TO THE PUBLIC ABOUT HEALTH PROTOCOLS IN THE ERA OF THE COVID-19 PANDEMIC - Kalila Anafah; Fadia Rohmatun Nisak; Rohmatul Intan Nur K; Violita Tryas Kaulika; Moses Glorino Rumambo Pandin (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The background of this research is that researchers, as students, want to contribute directly to the community to reduce the spread of Covid-19 in Indonesia. We contribute by distributing masks now to the community and socializing using posters on social media. The aim of this study was to determine their level of awareness and compliance with the established health protocol. The method used is a questionnaire data collection technique using google form with the population of East Java and a sample of people we can reach on the questionnaire and students with an average age of 19 years from several universities. The result based on the questionnaire shows that most people agree with the health protocol. They believe that they can immediately start an everyday life with the health protocol as before. However, based on the questionnaire data, some people still do not comply with the overall Health protocol.